Effects of potassium channel modulators on the responses of mammalian slowly adapting mechanoreceptors - Peter M.B. Cahusac; Solomon S. Senok (IBRO Neuroscience Reports, 2022)
Introduction: slowly adapting mechanoreceptors in the skin provide vital tactile information to animals. The ionic channels that underlie their functioning is the subject of intense research. Previous work suggests that potassium channels may play particular roles in the activation and firing of these mechanoreceptors. Objective: We used a range of potassium channel blockers and openers to observe their effects on different phases of mechanoreceptor responses. Methods: Extracellular recording of neural activity of slowly adapting mechanoreceptors was carried out in an in vitro preparation of the sinus hair follicles taken from rat whisker pads. A range of potassium (K+) channel modulators were tested on these mechanoreceptor responses. The channel blockers tested were: tetraethylammonium (TEA), barium chloride (BaCl2), dequalinium, 4-aminopyridine (4-AP), paxilline, XE 991, apamin, and charybdotoxin. Results: Except for charybdotoxin and apamin, these drugs increased the activity of both types of slowly adapting units, St I and St II. Generally, both spontaneous and evoked (dynamic and static) activities increased. The channel opener NS1619 was also tested. NS1619 clearly decreased evoked activity (both dynamic and static) while leaving spontaneous activity relatively unaffected, with no clear discrimination of effects on the two types of St receptor Conclusion: These findings are consistent with the targets of the drugs suggesting that K+ channels play an important role in the maintenance of spontaneous firing and in the production of and persistence of mechanoreceptor activity.